Association between HLA-DQ alleles and Leprosy in Indonesia Javanese population - Hardyanto Soebono, Hardyanto Soebono (Universitas Gadjah Mada, 1996)
Previous studies showed that susceptibility to leprosy and antibody response toward M. leprae in Javanese population was under control of HLA-DR alleles. To investigate whether this susceptibility was also associated with HLA-DQ, the study had been continued with phenotyping of HLA-DQ alleles and antibody assay to the same population which consisted of 79 leprosy patients, 41 tuberculoid (TT/BT) and 38 lepromatous (LL/BL) type, and 50 healthy controls. The HLA-DQ typing had been performed by using a sequence specific oligonucleotyping (SSO). method, while the anti M. leprae antibody had been tested by ELISA and INHIBITION-ELISA.The results show that HLA-DQB501 is associated with leprosy, either tuberculoid or lepromatous type (OR 3.27; 95% Cl 1.42-7.60). When all HLA-DQ1 alleles are analyzed, a significant association is found only with lepromatous leprosy (OR 9.18; 95% Cl 1.89-86.30). IgG antibody anti 36 kD M. leprae is found to be associated with HLA-DQ102. The level of this antibody is higher in HLA-DQ102 positive individuals compared to those negative one (P). No correlation is found between HLA-DQ alleles and the seropositivity of either IgM or IgG.In conclusion, the susceptibility to leprosy in this population is also controlled by genes in HLA-DQ locus. This study also supports the previous findings that HLA-DQ1 is a universal marker for the susceptibility to lepromatous leprosy, while the infection with M. leprae per se is not controlled by HLA genetic factor.Key words : leprosy - M. /eprae - genetic factor - HLA-DQ - HLA-DQ1 - HLA-DQB501